1995
DOI: 10.1083/jcb.128.5.893
|View full text |Cite
|
Sign up to set email alerts
|

The ryanodine receptor/calcium channel genes are widely and differentially expressed in murine brain and peripheral tissues.

Abstract: Abstract. Ryanodine receptors (RyRs) are intracellular calcium release channels that participate in controlling cytosolic calcium levels. At variance with the probably ubiquitous inositol 1,4,5-trisphosphate-operated calcium channels (1,4,5-trisphosphate receptors), RyRs have been mainly regarded as the calcium release channels controlling skeletal and cardiac muscle contraction. Increasing evidence has recently suggested that RyRs may be more widely expressed, but this has never been extensively examined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
506
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(537 citation statements)
references
References 63 publications
(98 reference statements)
29
506
1
1
Order By: Relevance
“…RyR1 was present in cerebellum, hippocampus and striatum, but it was not detected in mouse cortex. These results are in agreement with previous studies in murine brain (Giannini et al, 1995).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…RyR1 was present in cerebellum, hippocampus and striatum, but it was not detected in mouse cortex. These results are in agreement with previous studies in murine brain (Giannini et al, 1995).…”
Section: Discussionsupporting
confidence: 94%
“…RyR2 represents the predominant isoform in the CNS found in widespread brain regions (McPherson and Campbell, 1993;Giannini et al, 1995). Some studies indicate that RyR2, similarly to RyR3, is involved in the modulation of memory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Chavis et al have shown a similar signal in cerebellar granule cells [12], where RyRs activated by type-1 metabotropic glutamate receptors increase VACC activity. Since it has been reported that cerebellar granule cells possess RyR-2 and RyR-3 [5,6], the retrograde signal from RyR-2 or RyR-3 may target the L-type VACCs. Our results support and extend this novel idea that L-type VACCs and RyRs are functionally coupled, and we provide the first evidence for the involvement of cADPR in this coupling, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
“…cADP-ribose (cADPR) [3] has been suggested to be a second messenger or endogenous modulator for CICR [4], acting on specific subtypes of RyRs. The cardiac and brain isoforms of type-2 RyRs (RyR-2) and brain isoforms of type-3 RyRs (RyR-3) [5,6] are activated by cADPR [7,8], but the skeletal-muscle isoforms of type-1 RyRs (RyR-1) are not [8,9]. Whereas RyR-1 is coupled to L-type voltage-activated Ca# + channels (VACCs) through proteinprotein interactions [10], such direct coupling has not been shown in RyR-2 and RyR-3.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mRNA for Ryr3 has been detected in mammalian skeletal muscles [26,27]. However, the amount of the isoform is considered to be very minute, because only a single band corresponding to Ryrl is visible on SDS-PAGE of SR vesicles from these muscles in contrast to two bands which are observed in SR vesicles from bullfrog skeletal muscle.…”
Section: Z Murayama E Ogawalfebs Letters 380 (1996) 267-271mentioning
confidence: 99%